Implementasi Model Pembelajaran Course Review Horay (CRH) dalam Pembelajaran Sejarah Kebudayaan Islam di MIS Amaliyah Ar Ridho Deli Serdang - Syahri, Alfi; Harahap, Muhammad Riduan; Zuliana, Eka (Mauriduna: Journal of Islamic Studies, 2024)
Tujuan penelitian ini adalah untuk mengetahui: 1. Implementasi Model Pembelajaran Course Review Horay di MIS Amaliyah Ar Ridho Deli Serdang. 2. Pembelajaran Sejarah Kebudayaan Islam di MIS Amaliyah Ar Ridho Deli Serdang. 3. Faktor pendukung dan penghambat implementasi Model Pembelajaran Course Review Horay dalam pembelajaran Sejarah Kebudayaan Islam di MIS Amaliyah Ar Ridho Deli Serdang.. Jenis penelitian ini adalah kulitatif. Data penelitian diperoleh dari observasi, wawancara dan dokumentasi. Hasil Penelitian menunjukkan bahwa: 1.Implementasi Model Pembelajaran Course Review Horay (CRH) diterapkan dengan efektif dalam pembelajaran Sejarah Kebudayaan Islam di MIS Amaliyah Ar Ridho mencakup kegiatan Review materi, kuis atau permainan, serta umpan balik yang dilakukan secara terstruktur. Perencanaan dan persiapan yang matang, serta dukungan dari fasilitas dan antusiasme guru, menjadi kunci keberhasilan metode ini. 2. Pembelajaran Sejarah Kebudayaan Islam di MIS Amaliyah Ar Ridho Deli Serdang diterima dengan baik oleh siswa, dengan banyak di antara mereka menghargai metode pembelajaran yang interaktif dan kreatif. Siswa menganggap topik-topik tertentu menjadi lebih menarik.3. Faktor Pendukung implementasi Model Pembelajaran Course Review Horay dalam pembelajaran Sejarah Kebudayaan Islam di MIS Amaliyah Ar Ridho Deli Serdang adalah, antusiasme guru, keterlibatan aktif siswa, dan dukungan fasilitas: Sedangkan faktor penghambat diantaranya pengelolaan waktu, perbedaan kemampuan siswa:dan keterbatasan fasilitas berupa masalah teknis dengan fasilitas dapat mengganggu jalannya kegiatan CRH. The purpose of this study is to determine: 1. Implementation of Course Review Horay Learning Model at MIS Amaliyah Ar Ridho Deli Serdang. 2. Learning Islamic Cultural History at MIS Amaliyah Ar Ridho Deli Serdang. 3. Supporting and inhibiting factors for the implementation of Course Review Horay Learning Model in learning Islamic Cultural History at MIS Amaliyah Ar Ridho Deli Serdang. This type of research is qualitative. Research data were obtained from observation, interviews and documentation. The results of the study show that: 1. The implementation of the Course Review Horay (CRH) learning model is effectively applied in learning the History of Islamic Culture at MIS Amaliyah Ar Ridho including reviewing material, quizzes or games, and feedback that is carried out in a structured manner. Thorough planning and preparation, as well as support from facilities and teacher enthusiasm, are the keys to the success of this method. 2. Learning the History of Islamic Culture at MIS Amaliyah Ar Ridho Deli Serdang is well received by students, with many of them appreciating the interactive and creative learning methods. Students consider certain topics to be more interesting. 3. Supporting factors for the implementation of the Course Review Horay learning model in learning the History of Islamic Culture at MIS Amaliyah Ar Ridho Deli Serdang are teacher enthusiasm, active student involvement, and support from facilities: While inhibiting factors include time management, differences in student abilities: and limited facilities in the form of technical problems with facilities that can interfere with the course of CRH activities